Edukasi Pertolongan Pertama Pada Kecelakaan (P3K) Bagi Palang Merah Remaja (PMR) Meningkatkan Kesiapan Menolong Korban Kecelakaan (First Aid Education for Youth Red Cross Improve Readiness to Help Accident Victim) - Retno Lusmiati Anisah; Parmilah Parmilah (Jurnal Kesehatan, 2020)
Accidents can happen anywhere and anytime, especially at school. There is a grace period that must be filled by a trained first aid until the victim is helped by medical personnel. First Aid for Accidents (P3K) at school, often provided by members of the Youth Red Cross (PMR). PMR's knowledge and attitude will affect the speed and accuracy in helping victims. Complications or disabilities due to accidents at school can be prevented if first aid is provided quickly and precisely. Several studies have found that the behavior of helping accident victims among students tends to be low, as is the case for PMR Wira members. The purpose of this scientific article is to determine the effect of education about first aid on the readiness to help PMR Wira members. This scientific paper uses a one group pre test post test design research design. The sample technique used was purposive sampling method of 32 respondents. Collecting data using a valid and reliable help readiness questionnaire. Data analysis using the Wilcoxon test.  Readiness to help before being given education was at a sufficient level and less, respectively, as many as 16 students (50%), and as many as 32 students (100.0%) were at a good level after being given education about first aid.  There is a significant difference in the level of readiness to help PMR Wira members before and after being given intervention (p = 0.000 <0.05). The results of the study are expected to be a reference for community nurses to develop nursing care in the school area, especially in increasing the readiness to help accident victims for students who are members of PMR Wira, with education on P3K on an ongoing basis. Kecelakaan dan dapat terjadi dimana dan kapan saja terutama di sekolah. Ada masa tenggang yang harus diisi oleh penolong pertama terlatih sampai korban ditolong oleh tenaga medis. Pertolongan Pertama pada Kecelakaan (P3K) di sekolah, seringkali diberikan oleh  anggota Palang Merah Remaja (PMR). Pengetahuan dan sikap PMR akan mempengaruhi kecepatan dan ketepatan dalam menolong korban. Komplikasi atau kecacatan akibat kecelakaan di sekolah bisa dicegah jika pertolongan pertama diberikan dengan cepat dan tepat. Beberapa penelitian menemukan bahwa perilaku menolong korban kecelakaan pada siswa cenderung rendah, begitu pula pada anggota PMR Wira.  Penelitian ini bertujuan untuk mengetahui pengaruh edukasi tentang P3K terhadap  kesiapan menolong anggota PMR Wira.  Karya tulis ilmiah ini menggunakan desain penelitian one group pre test post test design. Tehnik sampel yang digunakanan dengan metode purposive sampling sebanyak 32 responden. Pengumpulan data menggunakan kuesioner kesiapan menolong yang sudah valid dan reliabel. Analisa data menggunakan Wilcoxon test. Kesiapan menolong sebelum diberikan edukasi berada pada tingkat cukup dan kurang masing-masing sebanyak 16 siswa (50%), dan sebanyak 32 siswa (100,0%) berada pada tingkat baik sesudah diberikan edukasi tentang P3K.  Ada perbedaan yang signifikan pada tingkat kesiapan menolong anggota PMR Wira sebelum dan sesudah diberikan intervensi (p= 0,000< 0,05). Hasil penelitian diharapkan bisa menjadi acuan bagi perawat komunitas untuk mengembangkan asuhan keperawatan di area sekolah, terutama dalam peningkatan kesiapan menolong korban kecelakaan bagi siswa anggota PMR Wira, dengan edukasi tentang P3K secara berkelanjutan.